Prevention and Treatment of Pressure Ulcers in Stroke Patients at ICU - Primalia, Pudika; Hudiyawati, Dian (Universitas Muhammadiyah Surakarta, 2020)
Pressure ulcers are local tissue necrosis of the skin tissue and between bone protrusions, patients with stroke have a weakness in one or all limbs that causes patients to undergo treatment with bed rest so that a high risk of pressure ulcers. Treatment and recovery of pressure ulcers with bundle care are given as nursing actions to protect skin integrity. The aims of this study to identify and analyze scientific evidence for the use of bundle care with five key elements. The research method used in the review literature in international articles published in 2015-2019, obtained the results of 5 articles that fit the inclusion criteria. A series of five key bundle care elements should be given from the beginning of the patient being treated.